Interdisciplinary approach in the study of objects of visual anthropology (Abylkhan Kasteev’s watercolors as case study) (Journal of Philosophy Culture and Political Science, 2019)
In foreign historiography, the active use of museum artifacts of various origins as a source data has become a scientific tradition. In domestic historical studies, this source category is practically not involved. In this regard, the issues of large-scale and in-depth study and entry into scientific circulation of museum collections as a unique corps of historical and cultural sources, which, as shown by foreign scientific practice, are characterized by both visibility and reliability, are actualized. The relevance andnovelty of the topic is explained by the need to introduce into the scientific circulation previouslyunknown not only to the general public, but also to the specialists of Abylkhan Kasteev’s works (1904-1973), as a special category of materials on culture and ethnography of the Kazakhs. The purpose of thestudy: the study of a series of watercolors of A. Kasteev as objects of visual anthropology on the historyand ethnography of the Kazakhs. Scientific and practical significance of the project: the study will expandthe source base for the study and creation of visual information not only on the history of the fine artsof Kazakhstan, but also on the ethnic culture of the Kazakhs. Research methods: a systematic approach,involving the study of genre and stylistic directions of A. Kasteev’s works from the point of view of theircause-and-effect relation; structural-semantic method, the alleged compositional analysis of watercolors(as a visual picture) of the artist in order to reveal their ethno-cultural content, the logic of building formbuildingelements, and the contextual approach – studying the process of creating watercolor works bythe author in the context of specific socio-cultural conditions. The result of the research will contributeto the development of the history and ethnography of the Kazakhs from the standpoint of the continuityof the domestic art with the worldview priorities of the Kazakh people, while the practical value is intheir application in the development of scientific works on the history of culture and art of Kazakhstan.Key words: history, culture, ethnography, visual arts, visual anthropology, artist, watercolor, drawing,tradition, museum.